The Increased Expression of CCL20 and CCR6 in Rectal Mucosa Correlated to Severe Inflammation in Pediatric Ulcerative Colitis. (27th January 2015) - Uchida, Keiichi; Koike, Yuhki; Hashimoto, Kiyoshi; Saigusa, Susumu; Inoue, Mikihiro; Otake, Kohei; Tanaka, Koji; Matsushita, Kohei; Okita, Yoshiki; Fujikawa, Hiroyuki; Araki, Toshimitsu; Mohri, Yasuhiko; et al.
Abstract : Background/Aims . The aim of this study is to clarify the differences of CCL20 and CCR6 expression, chemokine correlated to intestinal homeostasis, between pediatric and adult ulcerative colitis (UC) patients. Methods . Onehundred forty-one patients who underwent proctocolectomy were divided to two groups including childhood-onset UC (CUC, < 16 years old, n = 24 ) and adult-onset UC (AUC, ≧ 16 years old, n = 117 ) . A total of 141 formalin-fixed, paraffin-embedded tissue samples of rectum were obtained from these patients. Histological inflammation of rectum in resected specimen was evaluated by using Geboes histological assessment. In immunohistochemistry study, the CCL20 expression was evaluated by intensity and the stained area, and the CCR6 expression was evaluated by lymphocytes infiltration pattern. Results . CCL20 score and CCR6 positive lymphocytes infiltration pattern were statistically significantly correlated with histological inflammation severity of UC in all patients ( P < 0.05 ) . CCL20 and CCR6 expression in CUC were statistically significantly higher than that in AUC in all or pathologically severe cases ( P < 0.05 ) . Conclusions . CCL20 and CCR6 may play a significant role in local damage and pathological changes in UC especially pediatric patients. In the future, our understanding of the differences in CCL-CCR6 interaction between adults and children may lead to the pathogenesis of IBD.